À l’origine du culte du Précieux Sang de Fécamp, le Saint Voult de Lucques - Jean-Guy Gouttebroze (Tabularia)
After the Crucifixion, Nicodemus, accompanied by Joseph of Arimathaea, receives and buries the body of Christ. Nicodemus is one of the last people to have been in physical contact with Christ’s mortal remains, which he saw and touched. Because of this he is in a position to become a provider of relics. Inspired by God he chissels the face of Christ. This sculpture, the Holy Face, travels from the Holy Land to Lucca. According to a second tradition, Nicodemus receives the 'particules' or drops of Holy Blood, which, following a miraculous journey, shall be carried inside the trunk of a fig tree to the coast where in due course the monastery of Holy Trinity at Fécamp will arise. The two semi-historical traditions are not independent of each other. Several aspects suggest that the clergy and laity at Fécamp responsible for the translation narrative of the Holy Blood may also have made a contribution to story of the Holy Face of Lucca.